Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1164/rccm.201109-1686oc
|View full text |Cite
|
Sign up to set email alerts
|

Calpastatin Controls Polymicrobial Sepsis by Limiting Procoagulant Microparticle Release

Abstract: These results demonstrate an important role of the calpain/calpastatin system in coagulation/inflammation pathways during sepsis, because calpain inhibition is associated with less severe disseminated intravascular coagulation and better overall outcomes in sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
50
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 47 publications
5
50
0
1
Order By: Relevance
“…In the CLP model of sepsis, calpain activation peaked within the first 6 h of the immune response [31]. This study also showed that transgenic mice with ubiquitous overexpression of Calpastatin, showed reduced calpain activation and tissue damage following CLP [31]. Interestingly, similar defects in TNF-α and IL-1α production were noted in Calpastatin transgenic mice subjected to CLP [31], as we have observed here in FIP-treated calpain KO mice.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In the CLP model of sepsis, calpain activation peaked within the first 6 h of the immune response [31]. This study also showed that transgenic mice with ubiquitous overexpression of Calpastatin, showed reduced calpain activation and tissue damage following CLP [31]. Interestingly, similar defects in TNF-α and IL-1α production were noted in Calpastatin transgenic mice subjected to CLP [31], as we have observed here in FIP-treated calpain KO mice.…”
Section: Discussionsupporting
confidence: 82%
“…In endotoxemia models, calpain activation also leads to damage of cardiac, lung, and muscle tissues in mice [29,30,52]. In the CLP model of sepsis, calpain activation peaked within the first 6 h of the immune response [31]. This study also showed that transgenic mice with ubiquitous overexpression of Calpastatin, showed reduced calpain activation and tissue damage following CLP [31].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…However, previous studies describe both protective and deleterious effects [4,5]. Converging animal and clinical data have emphasized the role of procoagulant MPs in the initiation of disseminated intravascular coagulation (DIC) during sepsis [6][7][8]. Patients with meningococcal sepsis display elevated numbers of MPs originating from platelets and granulocytes that are prothrombotic [6].…”
mentioning
confidence: 99%